The The Effectiveness of Netflix Subtitles as a Learning Media for EFL Learners' Vocabulary: A Quasi-Experimental Study on EFL Learners - Wulandari, Agustina Putri (English Edu: Journal of English Teaching and Learning, 2025)
Vocabulary is fundamental to learning English, especially for EFL (English as a Foreign Language) students. This study aims to test the effectiveness of using Netflix Subtitles as a medium for learning vocabulary. The method used was quasi-experimental with a pretest-posttest design, involving 66 students divided into experimental and control classes. Students in the experimental class received three treatments using Netflix Subtitles. The analysis showed that using Netflix Subtitles significantly improved students' vocabulary mastery (H0 rejected, Ha accepted). These findings indicate that Netflix Subtitles are an effective learning medium for improving EFL students' vocabulary. Further research is recommended to explore additional variables, such as gender differences or academic levels, to understand the impact of this media on a more diverse population. Keywords: Vocabulary, EFL Learners, Netflix Subtitles